Border disease virus and chlamydophila abortus co-infection in aborted sheep foetuses - Şevik, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Abortion in sheep and goats is one of the most important reproductive problems that affect small ruminants breeding. Non-infectious factors and infectious agents such as bacterial, viral, mycotic and parasitic infectious agents can cause abortion in sheep and goats. A high rate of abortion (43.75%) was observed in two sheep flocks in Niğde Province in Turkey during the lambing season in 2016. To determine the reason of abortion, aborted sheep foetuses (n = 3) and EDTA whole blood samples (n = 3) from mother of the foetuses were collected from two sheep flocks. Aborted foetuses and buffy coat cells of the EDTA whole blood samples were used for total nucleic acid extraction. Extracted nucleic acids were analysed for akabane virus (AKAV), bluetongue virus (BTV), peste des petits ruminants virus (PPRV), pestiviruses, Schmallenberg virus (SBV), Brucella spp., Chlamydophila abortus (C. abortus), Coxiella burnetii and Listeria monocytogenes. Border disease virus (BDV) RNA and C. abortus DNA were detected in three aborted sheep foetuses whereas other investigated infectious agents were not detected. Additionally, EDTA whole blood samples from mother of the foetuses were also found BDV positive. To the best of my knowledge, this is the first report on BDV and C. abortus co-infection in aborted sheep foetuses.